Exploration of Pathways for Cultivating Creative Practice Within Core Competence of Music Education in Primary School Under the Perspective of New Curriculum Standards - Fu, Na (Journal of Educational Research and Policies, 2026)
The Compulsory Education Arts Curriculum Standards (2022 Edition) incorporates creative practice into the core competency framework for music education, marking a shift in primary school music pedagogy from traditional, singular creativity training towards competency-oriented, comprehensive skill development. This paper examines the conceptual and practical differences in music teaching before and after the new curriculum standards were issued. By integrating specific implementation strategies such as unit-based holistic teaching and cross-disciplinary integration, it explores pathways for implementing creative practice literacy on music classes in primary school. This provides teaching references for teachers to enhance students’ artistic innovation and comprehensive practical abilities.